TIPRL, a Novel Tumor Suppressor, Suppresses Cell Migration, and Invasion Through Regulating AMPK/mTOR Signaling Pathway in Gastric Cancer - Luan, Meng; Shi, Shan-Shan; Shi, Duan-Bo; Liu, Hai-Ting; Ma, Ran-Ran; Xu, Xiao-Qun; Sun, Yu-Jing; Gao, Peng (Frontiers in Oncology, 2020)
Invasion and metastasis of gastric cancer after curative resection remain the most common lethal outcomes. However, our current understanding of the molecular mechanism underlying gastric cancer metastasis is far from complete. Herein, we identified TOR signaling pathway regulator (TIPRL) as a novel metastasis suppressor in gastric cancer through genome-wide gene expression profiling analysis using mRNA microarray. Decreased TIPRL expression was detected in clinical gastric cancer specimens, and low TIPRL expression was correlated with more-advanced TNM stage, distant metastasis, and poor clinical outcome. Moreover, TIPRL was identified as a direct target of miR-216a-5p and miR-383-5p. Functional study revealed that re-expression of TIPRL in gastric cancer cell lines suppressed their migratory and invasive capacities, whereas inverse effects were observed in TIPRL-deficient models. Mechanistically, TIPRL downstream effectors and signaling pathways were investigated using mRNA microarray. Gene expression profiling revealed that TIPRL could not modulate the downstream genes at transcriptional levels, thereby implying that the regulation might occur at the post-transcriptional levels. We further demonstrated that TIPRL induced phosphorylation/activation of AMPK, which in turn attenuated phosphorylation of mTOR, p70S6K, and 4E-BP1, thereby leading to inactivation of mTOR signaling and subsequent suppression of cell migration/invasion in gastric cancer. Taken together, TIPRL acts as a novel metastasis suppressor in gastric cancer, at least in part, through regulating AMPK/mTOR signaling, likely representing a promising target for new therapies in gastric cancer.